Spatial monitoring of open caissons via computer vision approach - Qunwei Wang; Qun Li; Youliang Zhang (Scientific Reports)
Abstract Monitoring of the open caissons during the sinking process is a crucial aspect in construction projects. Traditional methods such as Electric Level have limitations in providing continuous monitoring throughout the sinking process. To address this challenge, this paper introduces a novel approach utilizing computer vision and linear intensity change model for 3D reconstruction of open caissons and real-time monitoring of the caisson sinking. In this proposed approach, RGB-D camera was firstly calibrated for the intrinsic and extrinsic parameters. Then 3D coordinates of the open caisson were obtained via the calibrated IR sensors of RGB-D camera. Subsequently, the spatial visual image of the open caisson for display was calculated using RGB sensors and the 3D coordinates. During sinking, multiple RGB sensors combined with a linear intensity change model were used for monitoring settlement displacement. The spatial visual image of the open caisson was updated with the data of the settlement and out-plane displacement. The feasibility and effectiveness of the proposed approach are validated by examples. This innovative monitoring solution has the potential to revolutionize the construction process in open caisson, ensuring timely detection of any deviations and facilitating proactive decision-making for optimal project outcomes.